Peran Kepuasan Pelanggan dalam Memediasi Pengaruh Servicescape terhadap Revisit Intention - Kenny Roz (Jurnal Bisnis dan Manajemen, 2021)
In the current millennial era, guiding business people, especially in the service sector, to provide the best service. This study aims to analyze the effect of servicescape on revisit intention with customer satisfaction as a mediating variabel. Data collection was obtained by distributing questionnaires online. The population in this study were visitors to Roketto cafe Malang with purposive sampling as a sample determination with the criteria of having visited at least once. The sample used in this study were 186 respondents. The research data were analyzed using path analysis techniques with analysis tools using Partial Least Square (PLS). The facts found in this study are servicescape has a positive and significant effect on customer satisfaction, customer satisfaction has a positive and significant effect on revisit intention, servicescape has a positive and significant effect on revisit intention, and servicescape has a positive and significant effect on revisit intention through customer satisfaction.